Design and Manufacture of Modular Robotic Cell prototype for application in different production processes - Rodríguez Gómez , Diego Alejandro; Arias Ardila , Wilson Leonardo; Torres , Camilo Andrés (I+ T+ C- Research, Technology and Science, 2023)
This work presents the design and development of a two-axis robotic cell with a modular and versatile approach for industrial applications. The aim is to enhance efficiency in industrial production through process automation. The modular design allows for future adaptations without significant structural changes. The results demonstrate an increase in production speed, a reduction in errors and waste, and greater consistency in product quality. The investment in this robotic cell is economically justified by its benefits. Safety measures have been implemented to ensure the integrity of operators. Additionally, various applications have been presented, such as the automation of manufacturing processes, painting, and parts organization. This project opens up opportunities for future research, such as process optimization, the integration of artificial intelligence, applications in Industry 4.0, and sustainability